1993
DOI: 10.1007/bf03160030
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia protects somatostatinergic neurons in rat dentate hilus from zinc accumulation and cell death after cerebral ischemia

Abstract: We have previously shown that somatostatin (SS) immunoreactive (-i) neurons, located in the rat dentate hilus, are vulnerable to cerebral ischemia (Johansen et al., 1987). Within 40 h after ischemia, the cells show clear signs of cell death. At the same time, we observed that dying cells, located in the projection field of the mossy fibers (dentate hilus and CA3 mossy fiber layer), accumulate free zinc. We now demonstrate that the hilar cells, accumulating zinc after ischemia, are SS-i cells. Since it is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Acid fuchsine again stained most neurons that were also TSQ-positive. Subsequent studies showed that intraischemic hypothermia (291C) inhibited both Zn 2 þ accumulation and cell death (Johansen et al, 1993). To date, only one peer-reviewed manuscript addresses the role of Zn 2 þ neurotoxicity after TBI (Suh et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…Acid fuchsine again stained most neurons that were also TSQ-positive. Subsequent studies showed that intraischemic hypothermia (291C) inhibited both Zn 2 þ accumulation and cell death (Johansen et al, 1993). To date, only one peer-reviewed manuscript addresses the role of Zn 2 þ neurotoxicity after TBI (Suh et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…Protection by low temperature has also been demonstrated experimentally in vivo [116,117], and hypothermia has also been shown to reduce OGD-induced neuronal cell death in hippocampal slice cultures [3,6,7,118].…”
Section: Oxygen-glucose Deprivation (Ogd)mentioning
confidence: 93%
“…Johansen and colleagues (10), as a follow-up to the original study conducted by Tonder and others (9) found that intra-ischemic hypothermia (29°C) Bicuculline alone: no effect.…”
Section: Neurotoxicity Of Zinc In Ischemiamentioning
confidence: 94%